Synthesis and analysis of ZnO and CdSe nanoparticles - Ashtaputre, S. S.; Deshpande, Aparna; Marathe, Sayali; Wankhede, M. E.; Chimanpure, J.; Pasricha, R.; Urban, J.; Haram, Santosh K.; Gosavi, S. W.; Kulkarni, S. K. (Pramana-Journal of Physics, 2005)
Zinc oxide and cadmium selenide particles in the nanometer size regime have been synthesized using chemical routes. The particles were capped using thioglycerol in case of ZnO and 2-mercaptoethanol in case of CdSe to achieve the stability and avoid the coalescence. Zinc oxide nanoparticles were doped with europium to study their optical properties. A variety of techniques like UV-Vis absorption spectroscopy, X-ray diffraction (XRD), photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR) and transmission electron microscopy (TEM) were used to carry out structural and spectroscopic characterizations of the nanoparticles.
Keywords: chemical capping; Doping; Nanoparticles; photoluminescence

Synthesis and molecular structure of a zinc complex of the vitamin K-3 analogue phthiocol - Kathawate, Laxmi; Sproules, Stephen; Pawar, Omkar; Markad, Ganesh; Haram, Santosh K.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2013)
The complex [Zn(phthiocol)(2)(H2O)(2)]; 1, where phthiocol is 2-hydroxy-3-methyl-1,4-naphthoquinone, has been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-vis spectroscopy, thermogravimetric (TG) analysis, electrochemical and single crystal X-ray diffraction studies. The v(C=O) stretch shifts to lower frequencies upon complexation of phthiocol to Zn2+. H-1 NMR spectra show an upfield shift of the benzenoid ring protons in 1. There is a bathochromic shift of the LMCT band in the UV-vis spectra of 1. Single crystal X-ray structure of 1 show distorted octahedral geometry around Zn2+. Two phthiocol ligands are in plane with the metal, while water molecules are trans to this plane. Coordination of deprotonated phthiocol ligands is `trans, trans' to Zn2+. Intra as well as intermolecular interactions are observed in 1. Molecules of 1 show three dimensional network through C-H center dot center dot center dot O and O-H center dot center dot center dot O interactions. Additional anodic peaks are observed in cyclic voltammogram of phthiocol ligand due to oxidation of reduced species formed during reduction. One-electron reduction of 1 is shown to be reversible and DFT studies define this redox event as ligand-centered. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: hydrogen bonding; Naphthoquinone; Phthiocol; Trans coordination; Vitamin K-3; Zinc complex